2017
DOI: 10.3390/genes8090222
|View full text |Cite
|
Sign up to set email alerts
|

RECQ1 Helicase Silencing Decreases the Tumour Growth Rate of U87 Glioblastoma Cell Xenografts in Zebrafish Embryos

Abstract: RECQ1 helicase has multiple roles in DNA replication, including restoration of the replication fork and DNA repair, and plays an important role in tumour progression. Its expression is highly elevated in glioblastoma as compared to healthy brain tissue. We studied the effects of small hairpin RNA (shRNA)-induced silencing of RECQ1 helicase on the increase in cell number and the invasion of U87 glioblastoma cells. RECQ1 silencing reduced the rate of increase in the number of U87 cells by 30%. This corresponded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…RECQL is involved in various types of DNA repair, including mismatch repair, NER, and direct repair. RECQL has been found to be overexpressed in many other tumors and plays a critical role in malignant progression and PARPi resistance and may serve as a potential prognostic or predictive factor for ovarian cancer (Li et al, 2016; Vittori et al, 2017; Viziteu et al, 2017). DMC1 has been reported to be an essential recombinase for meiotic homologous recombination and plays an important role in generating the diversity of genetic information.…”
Section: Discussionmentioning
confidence: 99%
“…RECQL is involved in various types of DNA repair, including mismatch repair, NER, and direct repair. RECQL has been found to be overexpressed in many other tumors and plays a critical role in malignant progression and PARPi resistance and may serve as a potential prognostic or predictive factor for ovarian cancer (Li et al, 2016; Vittori et al, 2017; Viziteu et al, 2017). DMC1 has been reported to be an essential recombinase for meiotic homologous recombination and plays an important role in generating the diversity of genetic information.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the following studies use seemingly unrelated types of cancer cell lines, however, the authors are usually trying to find correlations between in vitro and in vivo invasion abilities and general pathogenesis as well as the potential of cancer cells to metastasize in vivo. In the last decade, the most commonly studied types of solid tumors in zebrafish are melanoma [152], breast, prostate, colon, and pancreatic cancers [153] and glioblastoma [154]. Here, we will walk through the course of time and illustrate on the diversity of xenograft studies how zebrafish contributed to our understanding of tumorigenesis and helped to describe new potential therapeutics.…”
Section: Transplantation Models—allografts and Xenograftsmentioning
confidence: 99%
“…Zebrafish as a model for retinoblastoma [170] and glioblastoma [154,171,172,173,174] has been popular in the last couple of years. Many of these studies highlight the significance of zebrafish in finding novel treatment targets and evaluating cancer inhibitor efficacy in vivo.…”
Section: Transplantation Models—allografts and Xenograftsmentioning
confidence: 99%
“…Silencing RECQ1 in cancer cells induces cell death by mitotic catastrophe [ 60 ] and reduced tumor growth in mouse models [ 61 ]. Furthermore, using zebrafish as a model organism, a recent study demonstrated that silencing RECQ1 reduces the tumor growth rate of glioblastoma cells, U87 [ 62 ]. Transient depletion of RECQ1 using siRNA decreases cancer cell migration and invasion in breast cancer MDA-MB-231 cells by regulating the expression of genes associated with cancer progression [ 41 , 42 ].…”
Section: Association Of Recq1 Expression With Cancermentioning
confidence: 99%